THE USE OF SAGO RESIDUE FERMENTATION AGAINST PERFORMANS SHEEP - M T Siagian; M Tafsin; S Umar; E Mirwandhono; A H Daulay (Universitas Sumatera Utara, 2017)
Abstract. This study objective was to examine the quality of sago residue fermented with Effective microorganism 4 (EM4) on merino sheep performance. This research was conducted in Kec. Binjai City of North Sumatra. This research has been conducted for 3 months starting from October until December 2016 using 20 sheep merino with initial weight of 18.30 ± 1.16 kg. The design used in this study was a complete randomized design (RAL) with 4 treatments and 5 replications. This treatment consists of P0 (non-fermented sago residue 40%); P1 (20% sago residue of fermented + 20% non fermented sago residue); P2 (